PENGARUH KUNJUNGAN WISATAWAN DAN RATA-RATA PENGELUARAN WISATAWAN TERHADAP PAD DAN PERTUMBUHAN EKONOMI PROVINSI BALI - Septyana Putra, I Gede Dea Joendra; Karmini, Ni Luh; Wenagama, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
This study aims to analyze the effect of the number of tourist visits and the average tourist expenditure on the local income of Bali Province, to analyze the effect of the number of tourist visits, average tourist expenditure, and local income on the economic growth of Bali Province, and to analyze the role of income. native areas in mediating the effect of the number of tourist visits and the average tourist expenditure on the economic growth of Bali Province. The data used in this research is secondary data, with the method of observation by observing documents or secondary data sources that are related. This study uses time series data with a total of 30 years of observations from 1990-2019, with the analysis technique used is Path Analysis. This study shows the results that the number of tourist visits and the average tourist expenditure have a positive and significant effect on local income in Bali Province. The number of tourist visits, the average tourist expenditure and local revenue have a positive and significant effect on economic growth in Bali Province. Own-source revenue mediates the effect of the number of tourist visits and the average tourist expenditure on economic growth in Bali Province.